Economics, finance, and social inequality beyond the pandemic - Vázquez, Nitzia; Díaz-Mondragón, Manuel (Gestionar: revista de empresa y gobierno, 2022)
Mexico is a country with deep economic and social inequalities that existed before the pandemic, were accentuated by the health crisis, but, although some countries are already considering COVID-19 as an endemic disease, there is no evidence that the enormous economic, financial and social deterioration of the lower-income population can be recovered and if, on the contrary, that the gap between rich and poor will increase. Economic policy is usually evaluated by the evolution of GDP, inflation and unemployment rates, none of these indicators can be considered positive, so it is clear that the public policies that have been applied are not adequate. Using a qualitative - analytical methodology, we present the evolution of growth, inflation, unemployment, education, the real interest rate and the financial markets, in all of them, establishing the link with economic and social inequality.